ANALYSIS OF STUDENTS' LEARNING DIFFICULTIES ON THE CONCEPT OF BUFFER SOLUTION USING FOUR-TIER MULTIPLE CHOICE DIAGNOSTIC TEST - Muhammad Firdaus; Rusman Rusman; Zulfadli Zulfadli (Chimica Didactica Acta, 2021)
This study aims to determine the level of students' understanding of each indicator of the buffer solution material and to determine the most difficult indicator in understanding the buffer solution material using the Four-Tier Multiple Choice diagnostic test. This type of research uses a descriptive type of research using a qualitative approach. The subjects of this study were students of class XI Madrasah Aliyyah Swasta Darul Ihsan as many as 15 students who were selected using the simple random sampling technique. The research instrument used was the Four-Tier Multiple Choice diagnostic test instrument sheet and student interview sheets. The results of this study showed that the average percentage of students who understood the concept was 32.3%, did not understand the concept was 38.1%, misconception was 20.6% and the error was 9%. Based on this research, it was found that the most difficult indicator to understand is the indicator to determine the relationship between the buffer solution and the concept of chemical equation and the indicator to calculate the pH of the acid buffer solution. So it can be concluded that the students of class XI Madrasah Aliyyah Private Darul Ihsan have difficulty in understanding the material of the buffer solution.